Hubungan Senam Hamil dengan Nyeri Kontraksi pada Ibu Inpartu - Eka Purnama Sari; Laily Prima Monica (Journal of Ners and Midwifery, 2014)
Childbirth is a physiological process that is experienced by pregnant women in which the baby, placenta and membranes comes out of the mother's uterus. In the birthing process, there is the pain of labor contractions which can be overcome by doing pregnancy exercise. Method: The research design was correlational design. The research sample 13 mother in labour at BPS Sriwahyuni Jatinom Village, Kanigoro Subdistric, Blitar Regency. It was choosen using total sampling. The data was collected using questionnaire. The data was analysed using spearman rank. Result : The results showed by Spearman Rank correlation (Rho) that theÂ  r value = 0,864 and p value = 0,000. Discussion : By doing pregnancy exercise on the first active phase of inpartu mother, it was expected to increase mother knowledge dan skills so that could reduce the pain of contraction.